1978
DOI: 10.1073/pnas.75.3.1222
|View full text |Cite
|
Sign up to set email alerts
|

Changes in restricted human cellular DNA fragments containing globin gene sequences in thalassemias and related disorders

Abstract: Human cellular DNA fragments from cells of normal subjects and patients with thalassemia obtained by restriction enzyme digestion were analyzed for their globin gene content. The fragments were separated on agarose gels, trans-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

1978
1978
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(39 citation statements)
references
References 27 publications
1
38
0
Order By: Relevance
“…Thus, we could order the 5.5-, 3.7-, 2.1-, and 1.6-kb EcoRI fragments as 5' (3, 3' (3, 5' 6, and 3' 6 fragments, respectively. This order is in agreement with that of Mears et al (2).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Thus, we could order the 5.5-, 3.7-, 2.1-, and 1.6-kb EcoRI fragments as 5' (3, 3' (3, 5' 6, and 3' 6 fragments, respectively. This order is in agreement with that of Mears et al (2).…”
Section: Resultssupporting
confidence: 83%
“…Four fragments, 5.5, 3.7, 2.1, and 1.6 kb in length, were present in normal and hydrops DNA and absent in HPFH DNA, in which the #(-and 6-globin structural genes are deleted. These four fragments were derived from the (3-and 6-globin structural genes, both of which contain an EcoRI site in the coding sequences (2,12).…”
Section: Resultsmentioning
confidence: 99%
“…The hybridization signal was amplified as described by Woo et al (23). Positive plaques were rescreened and small-scale preparations of DNA were made (24 (26); this gives the normal DNA band pattern, whereas the aj30 allele is associated with the (at least) partial deletion of fl and a genes (27), producing the extra 3.4-kb EcoRI band (28). Previous studies on genomic DNA (5, 6) and cloned human globin genes (3) allowed us to assign each of the bands shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…2), the extent of hybridization to DNA-paper is usually 2-3 times greater than to DNA-nitrocellulose after the stringent washes (0.1 concentrated NaCI/Cit/0.1% sodium dodecyl sulfate at 500C for [1][2] (7) observed that anionic dextran polymers accelerate reannealing of DNA in solution. Although such compounds should also accelerate hybridization of probes to immobilized DNA, the net effect of using such polymers in two-phase hybridizations was not easy to predict because self-annealing of the probe and hybridization to the DNA-paper could have been accelerated to different extents and because the backgrounds might have increased.…”
Section: Kb (Lanes B-d)mentioning
confidence: 99%
“…Southern's procedure (1) for transferring restriction fragments from agarose gels to nitrocellulose has been an essential part of recent advances in analyzing and purifying many DNA fragments and has also been used more recently to identify mutant globin genes in individuals with thalessemia (2) or sickle cell trait (3). However, several aspects of this method have not yet been optimized: (i) Large restriction fragments are not transferred from agarose gels efficiently, and fragments smaller than 0.3-0.5 kilobase (kb) do not bind well to nitrocellulose.…”
mentioning
confidence: 99%